1985
DOI: 10.1136/bmj.291.6508.1547
|View full text |Cite
|
Sign up to set email alerts
|

Management of selected patients with hyperprolactinaemia by partial hypophysectomy.

Abstract: Results are reported in 35 patients with prolactinomas who underwent pituitary surgery within the past five years. After surgery prolactin concentrations became normal in 26 patients and symptoms were alleviated, and nine normal pregnancies were achieved in seven women, including all those who had complained of infertility. Normal prolactin concentrations were restored in 16 of 17 patients with tumours 5-19 mm in diameter but in only six of 11 with tumours <4 mm and four of seven with tumours >20 mm. Normal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 15 publications
2
10
1
2
Order By: Relevance
“…In 1983 Serri et al reported an incidence of apparent recurrence of hyperprolactinaemia in 50% of patients (12/24) with microprolactinoma five years postoperatively 2. Our findings1 and those of Scanlon et al3 and Bevan et al4 did not confirm this observation. Other American and European authors, however, have reported higher recurrence rates.…”
Section: Commentcontrasting
confidence: 64%
“…In 1983 Serri et al reported an incidence of apparent recurrence of hyperprolactinaemia in 50% of patients (12/24) with microprolactinoma five years postoperatively 2. Our findings1 and those of Scanlon et al3 and Bevan et al4 did not confirm this observation. Other American and European authors, however, have reported higher recurrence rates.…”
Section: Commentcontrasting
confidence: 64%
“…The superiority of endoscopic surgery for hormonal control of prolactinomas has not been conclusively demonstrated. In the literature, a wide range of different results are presented for tumors operated by the microsurgery technique (54-86%) [24,32,[38][39][40]. A randomized study comparing the results of the endoscopic endonasal technique versus the sublabial microsurgical approach demonstrated similar results in terms of prolactinoma resection and hormonal control [26].…”
Section: Prolactinomasmentioning
confidence: 79%
“…Remission rates in large series of surgically treated prolactinomas vary between 54% and 86%. [53][54][55][56] In this study, biochemical cure was achieved in 72.7% of patients.…”
Section: Prolactinomasmentioning
confidence: 94%